2014
DOI: 10.1111/ejn.12767
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein Ten‐m3 mediates topography and patterning of thalamostriatal projections from the parafascicular nucleus in mice

Abstract: The striatum is the key input nucleus of the basal ganglia, and is implicated in motor control and learning. Despite the importance of striatal circuits, the mechanisms associated with their development are not well established. Previously, Ten-m3, a member of the Ten-m/teneurin/odz family of transmembrane glycoproteins, was found to be important in the mapping of binocular visual pathways. Here, we investigated a potential role for Ten-m3 in striatal circuit formation. In situ hybridisation revealed a patchy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 92 publications
4
44
0
Order By: Relevance
“…The role of Teneurins in neuronal development has been vastly documented [4850], but their appearance in the field of oncology is recent and their phenotypic contribution to tumorigenesis and malignant progression is unclear. We previously identified Ten-2 as a potential biomarker for malignant mesothelioma [25], and found evidence for dysregulated expression of Ten-2 and Ten-4 in other cancers through search of in the literature and by mining transcriptomics datasets [24].…”
Section: Discussionmentioning
confidence: 99%
“…The role of Teneurins in neuronal development has been vastly documented [4850], but their appearance in the field of oncology is recent and their phenotypic contribution to tumorigenesis and malignant progression is unclear. We previously identified Ten-2 as a potential biomarker for malignant mesothelioma [25], and found evidence for dysregulated expression of Ten-2 and Ten-4 in other cancers through search of in the literature and by mining transcriptomics datasets [24].…”
Section: Discussionmentioning
confidence: 99%
“…While vision is clearly important for being able to detect the looming stimulus, the reduced latency of standard-housed KOs could also be due to other deficits which may also be ameliorated by EE from birth. We have previously shown that although quite mobile (Leamey et al, 2007), Ten-m3 KOs exhibit subtle deficits in motor learning (Tran et al, 2015) as well as kyphosis (Leamey et al, 2007). The increased latency to escape observed in KOs could, therefore, be a result of reduced motor ability.…”
Section: The Improved Performance Of Kos Enriched Form Birth Is Not Dmentioning
confidence: 96%
“…Roles for Odz2 and Odz3 have been demonstrated in establishing the topography and segregation of ipsilateral and contralateral afferents in the dLGN and of thalamic afferents in visual cortex (reviewed in [35]). More recently, Odz3 has also been shown to control topography of thalamostriatal projections [13]. …”
Section: Resultsmentioning
confidence: 99%
“…Many of these, including Ephrins/Eph-receptors, Netrins/DCC/Unc5s, Slits/Robos, Neuregulin-1/Erbb4, secreted semaphorins/ neuropilins and L1 cell adhesion molecules, mediate general processes such as avoidance of the hypothalamus, projection into the internal capsule and topographic organisation of thalamocortical and/or corticothalamic projections through this intermediate target region (reviewed in [8, 9]). By contrast, very few molecules have been found so far that mediate more specific connectivity relationships of particular thalamic nuclei, such as Cdh6 [10], or that control sub-organisation of projections within thalamic nuclei, such as Lrp8 [11] or Ten-m3/Odz3 [12], which also regulates topography of projections to striatum [13]. …”
Section: Introductionmentioning
confidence: 99%